Motives for using Kratom (Mitragyna speciosa Korth.) among regular users in Malaysia - Singh, Darshan; Narayanan, Suresh; Müller, Christian P.; Swogger, Marc T.; Chear, Nelson Jeng Yeou; Bin Dzulkapli, Eshal; Yusoff, Nur Sabrina Mohd; Ramachandram, Dinesh Sangarran; Leon, Francisco; Mccurdy, Christopher R.; Vicknasingam, Balasingam (Journal of Ethnopharmacology, 2019)
Ethnopharmacological relevance: The leaves of Mitragyna speciosa (Korth.) or kratom have been traditionally used in Malaysia and Thailand mainly to enhance work productivity, as a folk remedy for treating common ailments, and as a mood enhancer.
CRIS-Team WoS Importer:2019-03-06